Biodiversity Conservation and Sustainable Development: Ecological Assessment and Monitoring of Biodiversity in Nigeria - lsichei, Augustine O. (Nigerian National Committee for Man and the Biosphere (MAB), 2014)
The ecosystem comprises the biological' community together with its physical environment. Ecological energetics and nutrient dynamics depend on fluxes between living and non- living components of ecosystems. Ecosystem may thus be viewed as the next higher level of organization of living, things but they are not necessarily different from communities since no community can be studied in isolation from its physical environment.